Clinical, radiographic and bronchoscopic findings of tracheal collapse in a calf - Tumer, K. C.; Polat, E. (Hellenic Veterinary Medical Soc, 2022)
A six-day-old calf was presented to the Firat University Veterinary Teaching Hospital with a history of wheezing (noisy respiration) and dyspnea that worsens over exercise and drinking. The calf shown upper respiratory distress symptoms including extended head and neck, dilated nostrils, severe inspiratory stridor with characteristic goose-honk cough, and exophthalmos. Upon these findings, upper airway obstruction was suspected and cervical-thoracic radiographs and bronchoscopy were decided to be performed focusing to obtain detailed visualization of the upper respiratory tract. Thoracic radiograph, a significant tracheal lumenn arrowing was visible at the area of the thoracic inlet, beginning from the caudal cervical region (C5) and extending to the cranial thorax (T1). Also, severe dorsoventral narrowing was detected, approximately 15 cm after entering the tracheal lumen by the bronchoscope. A diagnosis of tracheal collapse was established based on clinical, radiographic, and bronchoscopic findings. It is important to remember that tracheal collapse should be considered in the differential diagnosis of calves that show symptoms from the upper respiratory tract such as extended head and neck, dilated nostrils, severe inspiratory stridor with characteristic goose-honk cough.
Keywords: Calf; inspiratory dyspnea; honking sound cough; tracheal collapse